Kata selection after the full adoption of the scoring system at the top-level karate competitions - Augustovicova, D.; Hadza, R. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. The new kata competition rules were implemented in 2019 with a one-year transition period. Problem and aim. The main goal of the study is to describe the selection and successfulness of selected types of kata performed at the 2021 WKF top-level karate competitions. The secondary goal is to find out if there is an association between gender and the kata selection, and differences in kata selection across the age categories from round to round. Methods. All performed types of kata during the eleven WKF top-level karate events of the season 2021 were recorded. Athletes` country, sex, age category, name of the performed kata, technical, athletic, and total score, promotion to the next round (pass or did not pass to the next round, or win/lose in medal bouts), and ranking were recorded. Descriptive statistics and the Chi-square tests for the analysis were used. A total of 2,579 kata ensembles were performed (1,263 in the male and 1,316 in the female cate- gory, 861 in the cadets, 741 in the juniors, 101 in the U21, and 876 in the seniors` categories). Results. The most performed kata in the season 2021 was: Gojushiho (503, 19.5 %), followed by Papuren (345, 13.4%) Anan Dai (287, 11,1%) Suparinpei (200, 7,8%), Chatanyara Kushanku (169, 7, 6.6%). The most successful kata in the first round was Kuru- runfa (75,3%). The highest average score had those types of kata which were performed rarely such as Kyan No Kushanku, Tomari Bassai, Kishimoto No Kushanku. The most unsuccessful kata to pass to the 2nd round was Chatanyara Kushanku (24.3%) and the lowest average score had Seizan (19.70±2.15). Conclusion. Coaches and athletes should select the kata carefully to raise the chance to pass to the next round. The higher chance to pass to the next round or win the medal bout have types of kata with high movement frequency or kata performed rarely. Coaches should differentiate the kata selection according to gender. It seems referees do not meaningfully evaluate performed kata ensem- bles but rather selected the best athletes for the next round.